Newly appointed directors in the boardroom: How do women and men differ? - Singh, Val; Terjesen, Siri; Vinnicombe, Susan (Elsevier Science B.V., Amsterdam., 2008)
This paper investigates the human capital profile of new appointees to corporate boards, exploring gender differences in education, profile and career experiences. Findings from a study of UK boards reveal that women are significantly more likely to bring international diversity to their boards and to possess an MBA degree. New male directors are significantly more likely to have corporate board experience, including CEO/COO roles, while new female appointees are significantly more likely to have experience as directors on boards of smaller firms. Our evidence contradicts the view reported by some chairmen that women lack adequate human capital for boardroom positions.
Keywords: Careers; Corporate governance; Female directors; Corporate boards; Diversity; Diversity; Female directors; FTSE 100; Gender; Glass ceiling; Human capital; Top management teams